Meta-type wholly aromatic polyamide fiber and manufacturing method thereof

The controlled water washing and spinning process for meta-aramid fibers addresses the challenges of high strength, elongation, and dyeability, resulting in fibers with improved toughness, low residual solvent, and excellent dyeability for protective clothing and textiles.

JP2025009124APending Publication Date: 2025-01-20TEIJIN LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2023111901
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing meta-aramid fibers face challenges in achieving high breaking strength, high elongation, low residual solvent content, and good dyeability while maintaining mechanical properties and flame retardance, which limits their suitability for protective clothing and other applications.

Method used

A spinning method that controls water washing conditions during the production of meta-type wholly aromatic polyamide fibers, involving specific temperature differences and multiple water washing stages, along with a wet spinning process using a controlled molecular weight polymer and inorganic salt concentration, to achieve fibers with high toughness and easy dyeability.

Benefits of technology

The method produces meta-aramid fibers with a toughness value of 15.0 or more, low residual solvent content, and a dyeing rate of 90% or more, ensuring strength, flexibility, and ease of dyeing, suitable for protective clothing and textiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009124000001
    Figure 2025009124000001
Patent Text Reader

Abstract

To provide a meta-aramid fiber which can be suitably used for protective clothing because of having low residual solvent, high breaking strength, high elongation and excellent dyeability in particular among the meta-aramid fibers having excellent properties such as heat resistance, flame retardancy and mechanical properties.SOLUTION: There is provided a meta-type wholly aromatic polyaramid fiber having a breaking strength of 4.0 cN / dtex or more as prescribed by JIS-L-1015, a toughness value of 15.0 or more as expressed by the square root of the product of breaking strength and breaking elongation, a residual solvent amount in the fiber of 0.1 mass% or less, and a dyeing rate of the fiber of 90% or more as measured by a specific method.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a meta-type wholly aromatic polyamide fiber having excellent properties such as heat resistance, flame retardancy, and mechanical properties, low residual solvent, high breaking strength, high elongation, and good dyeability, and a method for producing the same. [Background technology]

[0002] It has been well known that wholly aromatic polyamides produced from aromatic diamines and aromatic dicarboxylic acid dihalides have excellent heat resistance and flame retardancy, and among such wholly aromatic polyamides, fibers of meta-type wholly aromatic polyamides (hereinafter sometimes referred to as meta-aramids or meta-type aromatic polyamides), such as polymetaphenylene isophthalamide, are particularly useful as heat-resistant and flame-retardant fibers. Exhibiting these properties, they are used, for example, in disaster prevention and safety clothing applications such as protective clothing, and in industrial applications such as filters and electronic components.

[0003] In recent years, with the advancement of society, there has been an increasing need for lighter weight and higher strength in the above-mentioned applications, and spun yarns made of high-strength meta-aramid fibers having a fiber breaking strength of more than 4.0 cN / dtex are preferably used.

[0004] Furthermore, in each of the above applications, there is an increasing demand for further improvement in processability and fatigue resistance. In order to satisfy this demand, it is becoming necessary to improve the elongation while maintaining the breaking strength of the fiber, that is, to increase the toughness.

[0005] In particular, the elongation of fibers is one of the important factors in clothing applications, and clothing made of high elongation fibers exhibits flexibility, which leads to improved texture and comfort. Therefore, if a meta-aramid fiber having high elongation while satisfying the breaking strength can be obtained, the industrial value thereof would be extremely high.

[0006] It is also well known that meta-aramid is soluble in amide polar solvents and can be made into fibers from the polymer solution by methods such as dry spinning, wet spinning, and semi-dry and semi-wet spinning, but on the other hand, if the amide polar solvent remains in the fiber, it not only causes coloration or yellowing of the fiber in a high-temperature atmosphere, but also has a risk of adverse effects on the human body when used for clothing purposes. For this reason, the development of a spinning method that can obtain fibers with little residual solvent is important in the production of meta-aramid fibers.

[0007] Here, in the conventionally known dry spinning (for example, Patent Document 1), in the fibrous polymer solution spun out from the spinneret, the solvent evaporates and dries from near the surface of the formed fibrous material, so that a dense and strong skin layer is formed on the fiber surface. Therefore, even if the fibrous material is subsequently washed with water, it is difficult to sufficiently remove the residual solvent.

[0008] On the other hand, in wet spinning, a method has been developed that can effectively wash out residual solvent by suppressing the formation of a skin layer and forming a fine void structure inside the fiber. For example, (a) A method in which a meta-aramid polymer solution substantially free of salts is discharged into a coagulation bath containing an amide-based polar solvent and water, coagulated to form a fibrous material (filament), which is then stretched in a plastic stretching bath containing an amide-based polar solvent and water, followed by washing with water and heat treatment (Patent Documents 2, 3, 4, etc.); (b) A method in which a polymer solution consisting of meta-aramid and an amide-based polar solvent containing salts is discharged into a coagulation bath consisting of an amide-based polar solvent and water, and substantially free of salts, to coagulate the polymer into a porous linear body, which is then stretched in a plastic stretching bath consisting of an aqueous solution of an amide-based polar solvent, which is then washed with water and then heat-treated (Patent Document 5); (c) A method in which a meta-aramid polymer solution containing calcium chloride produced by solution polymerization in an amide polar solvent and neutralization with calcium hydroxide, calcium oxide, etc. and water is spun into an aqueous coagulation bath containing substantially no inorganic salts and an amide polar solvent concentration of 45 to 60 mass % to form a fibrous material (Patent Documents 6 and 7). Examples include:

[0009] The meta-aramid fibers produced by these spinning methods use a mixed solvent of an amide polar solvent and water as a coagulation bath, and in the coagulation process, the balance between the diffusion of the solvent out of the system from the filaments and the intrusion of the coagulation liquid components into the filaments is strictly controlled to form a very fine void structure and suppress the formation of a skin structure. As a result, it has been reported that the amount of residual solvent in the fibers after washing, drying, and heat treatment is 0.1 mass% or less, and that the fibers have the minimum strength required for each of the above applications.

[0010] However, this type of coagulation method using a mixed solvent of an amide-based polar solvent and water requires very strict setting of the temperature, coagulation liquid composition, and polymer molecular weight conditions, and since the coagulated yarn has a porous structure, the breaking strength is very weak, so that handling under special conditions is required to increase the strength by stretching.

[0011] In addition, in the above cited documents, the breaking elongation of the obtained fibers is often about 30%, and no meta-aramid fibers with high elongation have been reported. Therefore, in order to industrially obtain meta-aramid fibers with high toughness, i.e., high strength and high elongation while reducing the residual solvent, very strict process control is required, making stable production of meta-aramid fibers difficult.

[0012] Furthermore, in addition to the above, the following methods have been reported as wet spinning methods for meta-aramid fibers. For example, (d) A wet spinning method in which a meta-aramid polymer powder is redissolved in an amide-based polar solvent, and then a 15 to 25% by mass solution of a meta-type wholly aromatic polyamide is spun into an aqueous coagulation bath containing 35 to 45% by mass of a high-concentration inorganic salt to coagulate (Patent Document 8).

[0013] In the above method, when the spun fibrous polymer is introduced into an aqueous coagulation bath or an aqueous coagulation bath containing a high concentration of inorganic salt, the solvent is desorbed in one direction from near the surface of the fibrous polymer into the aqueous coagulation bath, forming a strong skin layer similar to that of dry spinning. Therefore, it is difficult to sufficiently remove the residual solvent in the fiber, but the skin layer gives high coagulated yarn strength, making stable production possible throughout the entire spinning process, and the final fiber strength exceeds 4.0 cN / dtex.

[0014] However, even with such spinning methods, no meta-aramid fiber that satisfies both high strength and high elongation, i.e., has been reported to have high toughness, and if a production method that achieves high strength, high elongation and a small amount of residual solvent could be developed, it would be extremely useful industrially.

[0015] Recently, applications of meta-type wholly aromatic polyamide fibers have been expanding rapidly in fields such as bedding, clothing, and interior design, taking advantage of their flame resistance and flame retardancy. In particular, in the field of clothing, in addition to flame resistance and flame retardancy, dyeability that allows for free selection of fiber colors is also required as an important performance from the viewpoint of design. However, meta-type wholly aromatic polyamide fibers have a problem in that they are difficult to dye by conventional methods due to their rigid polymer molecular chains.

[0016] In view of this, as a method for improving dyeability, a method has been proposed in which an alkylbenzenesulfonic acid onium salt is added to a spinning solution to obtain a meta-type aromatic polyamide fiber that is easily dyeable with a cationic dye (Patent Document 9). According to this method, a meta-type aromatic polyamide fiber having good dyeability with a cationic dye can be obtained. However, the fiber to which the onium salt is added is expensive.

[0017] Another report has proposed a method in which amorphous fibers having pores are formed, the fibers swollen with water are steam-heated, and the dye is diffused into the pores of the fibers to obtain fibers containing the dye throughout the entire fiber structure, and the fibers are then steam-heated at a temperature higher than the glass transition temperature for a sufficient period of time to collapse the pores, thereby irreversibly trapping the dye within the fibers and crystallizing the fibers (Patent Document 10).

[0018] According to this method, it is possible to obtain fibers with good dyeability, but not only is it necessary to perform a heat treatment using high-temperature steam, but the physical properties of the fibers before the treatment are so low that they cannot be used in practice, and there is a possibility that the fiber crystallization will be insufficient even after the treatment. It is generally known that a low degree of crystallinity of a wholly aromatic polyamide fiber leads to a decrease in strength, shrinkage under high-temperature conditions or during dyeing treatment, and a decrease in dimensional stability.

[0019] On the other hand, Patent Documents 11 and 12 propose a method for obtaining a meta-wholly aromatic polyamide fiber having high dyeability by appropriately adjusting the components or conditions of a coagulation bath so as to obtain a coagulation form having no skin core, plastically stretching the fiber at a specific magnification, passing through a washing step, and then carrying out a dry heat treatment at 260 to 330° C. According to this method, the fiber is crystallized in the range of 5 to 20% so as not to affect the dyeability, and then dyed to complete the crystallization, thereby ensuring the physical properties of the fiber. However, when it is assumed that raw fibers before dyeing are used, the above crystallinity is insufficient to exhibit heat resistance and low thermal shrinkage.

[0020] Recently, as in Patent Document 13, a method for producing an easily dyeable meta-type wholly aromatic polyamide fiber with a dyeing rate of 90% or more has been proposed, in which an amide-based polar solvent solution of a meta-type wholly aromatic polyamide with a controlled weight-average molecular weight is wet-spun. However, the breaking strength of the fiber is insufficient, being about 3.0 to 3.5 cN / dtex, and the toughness value described below is also insufficient. Thus, assuming that raw fibers are processed according to the purpose and a fiber product is produced, handling is required assuming a dyeing treatment, which narrows the range of applications of the fiber. In addition, when dyeability is increased by the method of the conventional technology, not only is sufficient mechanical properties of the raw fiber itself not exhibited, but high strength cannot be exhibited even after the dyeing treatment, that is, there is also the disadvantage that the toughness is reduced. [Prior art documents] [Patent documents]

[0021] [Patent Document 1] Special Publication No. 35-14399 [Patent Document 2] JP 2001-303365 A [Patent Document 3] JP 2003-301326 A [Patent Document 4] JP 2003-342832 A [Patent Document 5] JP 2005-232598 A [Patent Document 6] International Publication No. 2007 / 089008 Brochure [Patent Document 7] International Publication No. 2011 / 118022 Brochure [Patent Document 8] Special Publication No. 48-17551 [Patent Document 9] Japanese Patent Application Publication No. 08-081827 [Patent Document 10] Japanese Patent Application Laid-Open No. 62-184127 [Patent Document 11] JP 2010-084237 A [Patent Document 12] JP 2011-236543 A [Patent Document 13] Patent Publication No. 2021-080586 Summary of the Invention [Problem to be solved by the invention]

[0022] An object of the present invention is to provide a meta-type wholly aromatic polyamide fiber (also referred to as a meta-aramid fiber) which has excellent properties such as heat resistance, flame retardancy, and mechanical properties, and which has a low residual solvent content, high breaking strength, and high elongation and therefore can be suitably used for protective clothing applications, and which also has good dyeability and therefore has designability, and a method for producing the same. [Means for solving the problem]

[0023] As a result of extensive investigations aimed at solving the above problems, the present inventors have completed the present invention by a spinning technique in which the water washing conditions are skillfully controlled during the spinning of meta-type wholly aromatic polyamide.

[0024] That is, according to the present invention, 1. A meta-type wholly aromatic polyamide fiber, characterized in that the fiber has a breaking strength of 4.0 cN / dtex or more as specified in JIS-L-1015, a toughness value expressed as the square root of the product of the breaking strength and breaking elongation of the fiber of 15.0 or more, the amount of solvent remaining in the fiber being 0.1 mass% or less, and a dye exhaustion rate measured by the method described below of 90% or more. (dyeing rate) A dye solution containing 6% owf cationic dye (manufactured by Nippon Kayaku Co., Ltd., product name: Kayacryl Blue GSL-ED (B-54)), 0.3 mL / L acetic acid, 20 g / L sodium nitrate, 70 g / L benzyl alcohol as a carrier agent, and 0.5 g / L dyeing assistant (manufactured by Meisei Chemical Industry Co., Ltd., product name: Disper TL) as a dispersant is prepared. Next, a dyeing process is carried out for 60 minutes at 120°C with a bath ratio of the fiber to be measured to the dye solution of 1:40. After the dyeing process, reduction cleaning is carried out for 20 minutes at 80°C with a bath ratio of 1:20 using a treatment solution containing 2.0 g / L hydrosulfite, 2.0 g / L Amylazine D (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: Amylazine D), and 1.0 g / L sodium hydroxide, and the fiber is washed with water and dried to obtain a dyed fiber. The same volume of dichloromethane is added to the dyeing residual liquid after dyeing the fiber to be measured, and the residual dye is extracted. The absorbance of the extracted liquid is then measured at wavelengths of 670 nm, 540 nm, and 530 nm, and the dye concentration of the extracted liquid is calculated from the calibration curves for the above three wavelengths, which were created in advance from a dichloromethane solution with a known dye concentration, and the average of the concentrations at the above three wavelengths is taken as the dye concentration (C) of the extracted liquid. Using the dye concentration (Co) before dyeing, the value obtained by the following formula is the dye exhaustion rate (U). Dyeing rate (U)=[(Co-C) / Co]×100, 2. The method for producing meta-type wholly aromatic polyamide fibers according to item 1 above, characterized in that in the solution spinning, which includes a step of washing the fibers with water, the water temperature difference during the washing step is 40°C or more. 3. The method for producing a meta-type wholly aromatic polyamide fiber according to 2 above, which comprises at least two water-washing steps, the water temperature in the latter step being at least 40° C. higher than that in the former step. 4. The method for producing a meta-type wholly aromatic polyamide fiber according to 3 above, wherein in two successive water washing steps, the water temperature in the latter step is at least 40° C. higher than the water temperature in the immediately preceding previous step; and 5. A method for producing a meta-type wholly aromatic polyamide fiber according to any one of 2 to 4 above, wherein the fiber is obtained by a wet spinning method in which an amide-based polar solvent solution containing 1.0 to 10.0 mass % of an inorganic salt is spun from a meta-type wholly aromatic polyamide having a weight-average molecular weight of 200,000 to 600,000 and then coagulated, and the method further comprises a step of washing the fiber with water (water-washing step). Regarding. Effect of the Invention

[0025] According to the present invention, a meta-type wholly aromatic polyamide fiber having a small amount of residual solvent and a high toughness value of 15.0 or more, which is expressed as the square root of the product of the strength and elongation of the fiber, can be obtained, so that when the fiber is used for protective clothing, it exhibits strength and flexibility, leading to improved texture and comfort, and can be used favorably. In addition, since the amount of residual solvent contained in the fiber is small, not only is coloring and yellowing of the fiber suppressed in a high-temperature atmosphere, but there is no adverse effect on the human body when used for clothing. Furthermore, when the fiber is used for clothing, a textile product with the desired design can be easily obtained by dyeing treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The present invention will be described in detail below. The meta-type wholly aromatic polyamide constituting the meta-aramid fiber of the present invention is composed of a meta-type aromatic diamine component and a meta-type aromatic dicarboxylic acid component, and may be copolymerized with other copolymerization components such as para-type within a range that does not impair the object of the present invention.

[0027] In the present invention, meta-type wholly aromatic polyamides mainly composed of metaphenylene isophthalamide units are preferably used from the viewpoints of mechanical properties, heat resistance, and flame retardancy. In meta-type wholly aromatic polyamides composed of metaphenylene isophthalamide units, the metaphenylene isophthalamide units preferably account for 90 mol % or more of all repeating units, more preferably 95 mol % or more, and particularly preferably 100 mol.

[0028] Examples of meta-type aromatic diamine components that are raw materials for meta-type wholly aromatic polyamides include metaphenylenediamine, 3,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl sulfone, etc., and derivatives thereof having a substituent such as halogen or an alkyl group having 1 to 3 carbon atoms on the aromatic ring, such as 2,4-toluylenediamine, 2,6-toluylenediamine, 2,4-diaminochlorobenzene, 2,6-diaminochlorobenzene, etc. Among these, it is preferable to use only metaphenylenediamine, or a mixed diamine containing 85 mol % or more, preferably 90 mol % or more, and particularly preferably 95 mol % or more of metaphenylenediamine.

[0029] As a raw material of meta-type aromatic dicarboxylic acid component constituting meta-type wholly aromatic polyamide, for example, meta-type aromatic dicarboxylic acid halide can be mentioned. As meta-type aromatic dicarboxylic acid halide, isophthalic acid halide such as isophthalic acid chloride, isophthalic acid bromide, and derivatives having a substituent such as halogen or alkoxy group having 1 to 3 carbon atoms on the aromatic ring, for example, 3-chloroisophthalic acid chloride, etc. can be mentioned. Among them, isophthalic acid chloride itself, or mixed carboxylic acid halide containing isophthalic acid chloride at 85 mol% or more, preferably 90 mol% or more, particularly preferably 95 mol% or more.

[0030] Examples of the polymerization method of the above meta-aramid include a method of isolating a powder of polymetaphenylene isophthalamide polymer by contacting an organic solvent system (e.g., tetrahydrofuran) that is not a good solvent for the resulting polyamide containing metaphenylenediamine and isophthalic acid chloride with an aqueous solution system containing an inorganic acid acceptor and a soluble neutral salt (JP Patent Publication No. 47-10863), or a method of solution-polymerizing the above diamine and acid chloride in an amide-based polar solvent and then neutralizing with calcium hydroxide, calcium oxide, or the like (JP Patent Publication Nos. 8-74121 and 10-88421), but the method is not limited thereto.

[0031] The weight-average molecular weight of the meta-aramid used in the present invention is preferably in the range of 200,000 to 600,000 according to the analysis method described below. Furthermore, in order to obtain a fiber that satisfactorily achieves high strength and high elongation, a polymer having a weight-average molecular weight in the range of 400,000 to 600,000 is more preferable.

[0032] The polymer having the molecular weight specified in the present invention may be a mixture of a low molecular weight polymer and a high molecular weight polymer, and the weight average molecular weight of the polymer obtained by adjusting the mixing ratio may be within the range of the weight average molecular weight. For example, if a polymer having a weight average molecular weight of 200,000 and a polymer having a weight average molecular weight of 800,000 are mixed to obtain a total weight average molecular weight of 500,000, there is no problem in using the present invention. On the other hand, if the weight average molecular weight is less than 200,000, it may not be possible to obtain fibers having sufficient strength, and the target toughness value may not be achieved.

[0033] The meta-type wholly aromatic polyamide fiber of the present invention is produced by using the meta-aramid polymer obtained as described above, through, for example, the following steps: spinning solution preparation step, spinning / coagulation step, water washing step, boiling water drawing step, dry heat treatment step, and hot drawing step.

[0034] In the spinning solution preparation step, the meta-aramid polymer is dissolved in a solvent to prepare a spinning solution (dope). In preparing the spinning solution, an amide polar solvent is usually used, and examples of the solvent include N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), and dimethylacetamide (DMAc). Among these, it is preferable to use NMP or DMAc from the viewpoints of solubility and handling safety.

[0035] The solution concentration of the meta-aramid in the spinning solution may be appropriately selected from the viewpoints of the coagulation rate and the solubility of the polymer in the subsequent spinning and coagulation step, and is usually preferably in the range of 10 to 30% by mass, more preferably in the range of 15 to 25% by mass in order to achieve stable spinning. In the present invention, the dope contains the inorganic salt in an amount of preferably 1.0 to 10.0% by mass, more preferably 1.0 to 5.0% by mass, and further preferably 2.0 to 3.0% by mass.

[0036] If the inorganic salt content exceeds 10.0% by mass, the coagulation rate becomes too fast, and many voids are formed in the fiber, making it impossible to obtain a fiber with the desired physical properties. It is preferable to use a chloride salt such as calcium chloride, magnesium chloride, or lithium chloride as the inorganic salt. In the spinning and coagulation step, a wet spinning method is preferred in which the dope obtained above is spun into a coagulation liquid and coagulated.

[0037] The spinning device is not particularly limited, and a conventionally known wet spinning device can be used. As long as it can perform stable wet spinning, the number and arrangement of the spinneret spinning holes do not need to be particularly limited, and for example, a multi-hole spinneret for staple fibers having 10 to 30,000 holes and a spinning hole diameter of 0.03 to 0.2 mm may be used. The temperature of the dope when spun from the spinneret is preferably in the range of 20 to 90°C, more preferably 70 to 90°C.

[0038] The coagulation bath used to obtain the fiber of the present invention is an aqueous solution containing 30% by mass or more, preferably 35 to 45% by mass of an inorganic salt such as calcium chloride or magnesium chloride, and 1 to 20% by mass, preferably 3 to 15% by mass of an amide-based polar solvent, at a temperature in the range of 50 to 90° C. A method has also been devised in which an aqueous solution of an amide-based polar solvent that is substantially free of inorganic salts is used, but such a coagulation solution does not form a skin on the surface of the coagulated yarn, so that yarn with sufficient strength may not be obtained. The coagulated yarn thus obtained is thoroughly washed in a water washing bath and then sent to a boiling water drawing step.

[0039] In the water washing step, the water temperature difference during the water washing step must be 40°C or more, and the preferred water temperature difference is 40°C to 90°C, and the more preferred water temperature difference is 50°C to 90°C. If the temperature change is less than 40°C, the low residual solvent amount and easy dyeability, which are the goals of the present invention, cannot be achieved. If the temperature change is more than 90°C, the physical properties of the fiber are significantly reduced, and high toughness cannot be achieved. The time change in the water temperature difference is preferably within 5 seconds, and more preferably within 3 seconds. For example, it is preferable to have at least two water washing steps, and the water temperature of the latter step is 40°C or more higher than that of the former step, and is preferably 40°C to 90°C higher. Furthermore, in two consecutive water washing steps, the water temperature of the latter step is preferably 40°C or more higher than that of the immediately preceding former step, and is more preferably 40°C to 90°C higher. In addition to the above, it is more preferable that the water temperature is 50 to 90°C higher.

[0040] When the water temperature is high, the washing or immersion time of the fiber is preferably 3 seconds or more, and more preferably 5 seconds or more. It is better that the immersion time of the fiber when the water temperature is high is as long as possible, but in consideration of productivity and cost, it is preferably 60 seconds or less.

[0041] The draw ratio in the boiling water drawing bath in the boiling water drawing step following the water washing step is preferably 1.5 to 5.0 times, more preferably 2.0 to 4.0 times. In the present invention, drawing is performed within this range of draw ratio to increase the molecular chain orientation, thereby ensuring the strength of the final fiber. Here, the "boiling water" in the "boiling water drawing step" does not necessarily have to be boiling, and is preferably 85°C or higher, more preferably 90°C or higher.

[0042] The fibers that have been subjected to the above washing and boiling water drawing steps are preferably subjected to a boiling water washing step and a dry heat treatment step. In the dry heat treatment step, the fibers that have been washed in the above steps are dry heat treated at a temperature preferably in the range of 100 to 250°C, more preferably 100 to 200°C. Here, the dry heat treatment is not particularly limited, but is preferably performed at a fixed length. The temperature of the above dry heat treatment refers to the set temperature of a fiber heating means such as a hot plate or a heated roller.

[0043] In the present invention, the fiber that has been subjected to the dry heat treatment step is subjected to a hot drawing step. In the hot drawing step, drawing is performed while applying heat treatment at 300 to 380° C. The draw ratio is preferably 1.2 to 5.0 times, and more preferably 1.5 to 3.5 times.

[0044] The toughness value of the meta-aramid fiber obtained by the above method is 15.0 or more, and the residual solvent content is 0.1 mass% or less. The toughness value must be 15.0 or more, and is preferably 16.0 or more. If the toughness value is 15 or more, a meta-type wholly aromatic polyamide fiber with high toughness, which is the target of the present invention, can be obtained, and when the fiber is used for clothing applications, it exhibits strength and flexibility, leading to improved texture and comfort, and can be used preferably.

[0045] The residual solvent content must be 0.1% by mass or less, and preferably 0.05% by mass or less. If the residual solvent content exceeds 0.1% by mass, not only will the fibers be discolored or yellowed in a high-temperature atmosphere, but there is also concern that the fibers may be adversely affected by the human body when used in clothing applications.

[0046] The breaking strength of the meta-aramid fiber obtained by the present invention must be 4.0 cN / dtex or more, and is preferably 4.0 cN / dtex or more and 5.5 cN / dtex or less. If the strength is less than 4.0 cN / dtex, problems such as a decrease in durability of the product in more advanced applications will occur. If the strength exceeds 5.5 cN / dtex, the breaking elongation will decrease, and high toughness will not be achieved.

[0047] Furthermore, the single fiber fineness of the meta-aramid fiber obtained by the present invention is preferably 0.5 to 10.0 dtex. If the fineness is less than 0.5 dtex, the processability is poor, and if the fineness is more than 10.0 dtex, the single yarn is too thick and the target residual solvent amount may not be achieved.

[0048] The dyeing rate of the dyed fiber of the meta-aramid fiber obtained by the present invention, as measured by the measurement method described below, must be 90% or more, preferably 90% to 99%, and more preferably 92% to 99%. If the dyeing rate is less than 90%, it is not preferable in terms of aesthetics required in the clothing field, and it is not possible to dye the fiber in the desired hue, and problems arise in the dyeing process, such as the need for a large amount of dye and processing time. EXAMPLES

[0049] The present invention will be described in detail below with reference to examples and comparative examples, but the scope of the present invention is not limited to the following examples and comparative examples. The physical properties in the examples and comparative examples were measured by the following methods.

[0050] [Weight average molecular weight Mw] According to JIS-K-7252, the analysis was performed using a high-performance liquid chromatography apparatus equipped with a size exclusion chromatography column, and the measurement was performed using dimethylformamide (containing 0.01 mol% lithium chloride) as the developing solvent. Note that a Sigma-Aldrich polystyrene set (peak top molecular weight Mp = 400 to 2,000,000) was used as the standard molecular weight sample.

[0051] [Single fiber size] Measurements were carried out in accordance with JIS-L-1015, Method A for corrected fineness, and the apparent fineness was expressed.

[0052] [Breaking strength, breaking elongation] Measurements were performed using a tensile tester (Instron, Model: 5565) under the following conditions based on JIS-L-1015. (Measurement conditions) Grip distance: 20mm Initial load: 0.044cN (1 / 20g / dtex) Pulling speed: 20mm / min

[0053] [Toughness value] The toughness value is expressed as the square root of the product of the breaking strength and breaking elongation of the fiber, and was calculated according to the following formula using the breaking strength (cN / dtex) and breaking elongation (%) measured by the above method. Toughness value = (breaking strength x breaking elongation) 1 / 2

[0054] [Residual solvent content] The amount of residual solvent was measured by pyrolysis gas chromatography using 1 mg of fiber. The amount of solvent was calculated from the peak area of ​​a calibration curve prepared using a standard sample.

[0055] [Dyeing rate] The "dye exhaustion rate" is determined by the following method. A dye solution containing 6% owf cationic dye (manufactured by Nippon Kayaku Co., Ltd., product name: Kayacryl Blue GSL-ED (B-54)), 0.3 mL / L acetic acid, 20 g / L sodium nitrate, 70 g / L benzyl alcohol as a carrier agent, and 0.5 g / L dyeing assistant (manufactured by Meisei Chemical Industry Co., Ltd., product name: Disper TL) as a dispersant is prepared.

[0056] Next, a dyeing process is carried out for 60 minutes at 120°C with a bath ratio of the fiber to be measured to the dye solution of 1:40. After the dyeing process, reduction cleaning is carried out for 20 minutes at 80°C with a bath ratio of 1:20 using a treatment solution containing 2.0 g / L hydrosulfite, 2.0 g / L Amylazine D (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: Amylazine D), and 1.0 g / L sodium hydroxide, and the fiber is washed with water and dried to obtain a dyed fiber.

[0057] The same volume of dichloromethane is added to the dyeing residual liquid after dyeing the fiber to be measured, and the residual dye is extracted. The absorbance of the extracted liquid is then measured at wavelengths of 670 nm, 540 nm, and 530 nm, and the dye concentration of the extracted liquid is calculated from the calibration curves for the above three wavelengths created in advance from a dichloromethane solution with a known dye concentration. The average concentration at the above three wavelengths is taken as the dye concentration (C) of the extracted liquid. The value obtained by the following formula using the dye concentration (Co) before dyeing is taken as the dye exhaustion rate (%). Dyeing rate (%)=[(Co-C) / Co]×100

[0058] [Example 1] A meta-aramid polymer powder having a weight average molecular weight of 500,000 synthesized by interfacial polymerization and calcium chloride powder were dissolved in N-methyl-2-pyrrolidone (NMP) to obtain a transparent polymer solution. At this time, the mass concentration of the meta-aramid polymer was adjusted to 22% and that of calcium chloride to 2.5% relative to the polymer solution.

[0059] This polymer solution was heated to 80°C and used as a spinning dope, which was discharged from a circular spinneret with 100 discharge holes each having a hole diameter of 0.1 mm into a coagulation bath at 80°C for spinning. The composition of this coagulation bath was 40% by mass of calcium chloride, 3% by mass of NMP, and the remaining 57% by mass of water. The yarn was passed through an immersion length (effective coagulation bath length) of 120 cm at a yarn speed of 5.0 m / min, and then drawn out into the air.

[0060] The solidified yarn was washed in the first and second water washing baths, with a total immersion time of 250 seconds. The first and second water washing baths had temperatures of 20°C and 30°C, respectively. Next, the washed yarn was immersed in hot water at 90°C in the third water washing bath, with an immersion time of 5 seconds. The movement time between each water washing bath was 3 seconds. Next, following this water washing step, the yarn was stretched 2.0 times in boiling water at 90°C as a boiling water drawing step, and then immersed in boiling water at 90°C for 40 seconds as a boiling water washing step, and washed after boiling.

[0061] The fiber was then wound around a roller having a surface temperature of 170° C. for dry heat treatment, and then stretched 1.5 times using a hot plate having a surface temperature of 340° C. to obtain meta-type wholly aromatic polyamide fibers. The obtained fiber had a fineness of 2.1 dtex, a breaking strength of 4.9 cN / dtex, a breaking elongation of 50%, and a toughness value of 16. In addition, the amount of residual solvent was 0.03% by mass, and the degree of exhaustion was 95%.

[0062] [Comparative Example 1] A meta-type wholly aromatic polyamide fiber was obtained by the same production method as in Example 1, except that the washed yarn was immersed in 50°C warm water instead of 90°C hot water in the third water washing bath. The obtained fiber had a fineness of 2.0 dtex, a breaking strength of 5.0 cN / dtex, a breaking elongation of 51%, and a toughness value of 16. In addition, the amount of residual solvent was 0.79% by mass, and the degree of exhaustion was 70%.

[0063] [Example 2] A meta-aramid polymer powder having a weight average molecular weight of 520,000 synthesized by interfacial polymerization was dissolved in N-methyl-2-pyrrolidone (NMP) to obtain a transparent polymer solution. At this time, the mass concentration of the meta-aramid polymer was adjusted to 22% and calcium chloride to 2.0% relative to the polymer solution.

[0064] This polymer solution was heated to 80°C and used as a spinning dope, which was discharged from a circular spinneret with 100 discharge holes each having a hole diameter of 0.1 mm into a coagulation bath at 80°C for spinning. The composition of this coagulation bath was 40% by mass of calcium chloride, 3% by mass of NMP, and the remaining 57% by mass of water. The yarn was passed through an immersion length (effective coagulation bath length) of 120 cm at a yarn speed of 5.0 m / min, and then drawn out into the air.

[0065] The solidified yarn was washed in the first and second water washing baths, with a total immersion time of 250 seconds. The first and second water washing baths had temperatures of 20°C and 30°C, respectively. Next, the washed yarn was immersed in hot water at 90°C in the third water washing bath, with an immersion time of 30 seconds. The movement time between each water washing bath was 3 seconds. Next, following this water washing step, the yarn was stretched 2.0 times in boiling water at 90°C as a boiling water drawing step, and then immersed in boiling water at 90°C for 40 seconds as a boiling water washing step, and washed after boiling.

[0066] The fiber was then wound around a roller having a surface temperature of 170° C. for dry heat treatment, and then stretched 1.5 times using a hot plate having a surface temperature of 340° C. to obtain meta-type wholly aromatic polyamide fibers. The obtained fiber had a fineness of 2.1 dtex, a breaking strength of 4.2 cN / dtex, a breaking elongation of 64%, and a toughness value of 16. In addition, the amount of residual solvent was 0.01% by mass, and the degree of exhaustion was 96%.

[0067] [Comparative Example 2] A meta-type wholly aromatic polyamide fiber was obtained by the same production method as in Example 2, except that the washed yarn was immersed in 50°C warm water instead of 90°C hot water in the third water washing bath. The obtained fiber had a fineness of 2.1 dtex, a breaking strength of 4.4 cN / dtex, a breaking elongation of 60%, and a toughness value of 16. In addition, the amount of residual solvent was 0.30% by mass, and the degree of exhaustion was 79%.

[0068] [Example 3] A meta-aramid polymer powder having a weight average molecular weight of 510,000 synthesized by interfacial polymerization and calcium chloride powder were dissolved in N-methyl-2-pyrrolidone (NMP) to obtain a transparent polymer solution. At this time, the mass concentration of the meta-aramid polymer was adjusted to 22% and that of calcium chloride to 2.5% relative to the polymer solution.

[0069] This polymer solution was heated to 80°C and used as a spinning dope, which was discharged from a circular spinneret with 100 discharge holes each having a hole diameter of 0.1 mm into a coagulation bath at 80°C for spinning. The composition of this coagulation bath was 40% by mass of calcium chloride, 3% by mass of NMP, and the remaining 57% by mass of water. The yarn was passed through an immersion length (effective coagulation bath length) of 120 cm at a yarn speed of 5.0 m / min, and then drawn out into the air.

[0070] The solidified yarn was washed in the first and second water washing baths, with the total immersion time being 250 seconds. The first and second water washing baths had temperatures of 20°C and 30°C, respectively. Next, the washed yarn was immersed in hot water at 80°C in the third water washing bath, with the immersion time being 30 seconds. The movement time between each water washing bath was 3 seconds. Next, following this water washing step, the yarn was stretched 2.0 times in boiling water at 90°C as a boiling water drawing step, and then immersed in boiling water at 90°C for 40 seconds as a boiling water washing step, and washed after boiling.

[0071] The fiber was then wound around a roller having a surface temperature of 170° C. for dry heat treatment, and then stretched 1.5 times using a hot plate having a surface temperature of 340° C. to obtain meta-type wholly aromatic polyamide fibers. The obtained fiber had a fineness of 2.2 dtex, a breaking strength of 4.3 cN / dtex, a breaking elongation of 64%, and a toughness value of 17. In addition, the amount of residual solvent was 0.03% by mass, and the degree of exhaustion was 94%.

[0072] [Comparative Example 3] A meta-type wholly aromatic polyamide fiber was obtained by the same production method as in Example 3, except that the washed yarn was immersed in 80°C warm water in the first water washing bath and in 20°C water in the third water washing bath. The obtained fiber had a fineness of 2.1 dtex, a breaking strength of 4.2 cN / dtex, a breaking elongation of 60%, and a toughness value of 16. In addition, the amount of residual solvent was 0.40% by mass, and the degree of exhaustion was 75%.

[0073] [Example 4] A meta-type wholly aromatic polyamide fiber was obtained by the same production method as in Example 1, except that the washed yarn was immersed in 70°C warm water instead of 90°C hot water in the third water washing bath. The obtained fiber had a fineness of 2.0 dtex, a breaking strength of 4.9 cN / dtex, a breaking elongation of 51%, and a toughness value of 16. In addition, the amount of residual solvent was 0.08% by mass, and the degree of exhaustion was 92%.

[0074] [Example 5] A meta-type wholly aromatic polyamide fiber was obtained by the same production method as in Example 1, except that 50°C water was used in the second washing bath and the washed yarn was immersed in 80°C warm water in the third washing bath. The obtained fiber had a fineness of 1.9 dtex, a breaking strength of 4.8 cN / dtex, a breaking elongation of 50%, and a toughness value of 15. In addition, the residual solvent amount was 0.10% by mass, and the dye exhaustion rate was 91%.

[0075] [Comparative Example 4] A meta-type wholly aromatic polyamide fiber was obtained by the same production method as in Example 1, except that hot water at 90°C was used in the first water washing bath, water at 30°C was used in the second water washing bath, and the washed yarn was immersed in water at 50°C in the third water washing bath. The obtained fiber had a fineness of 2.2 dtex, a breaking strength of 4.3 cN / dtex, a breaking elongation of 42%, and a toughness value of 13. In addition, the amount of residual solvent was 0.31% by mass, and the degree of exhaustion was 78%.

[0076] [Comparative Example 5] A meta-type wholly aromatic polyamide fiber was obtained by the same production method as in Example 1, except that 60°C warm water was used in the first water washing bath, 80°C warm water was used in the second water washing bath, and the washed yarn was immersed in 90°C hot water in the third water washing bath. The obtained fiber had a fineness of 2.1 dtex, a breaking strength of 3.5 cN / dtex, a breaking elongation of 30%, and a toughness value of 10. In addition, the residual solvent amount was 0.11% by mass, and the dye exhaustion rate was 90%.

[0077] [Table 1] [Industrial Applicability]

[0078] According to the present invention, meta-aramid fibers having excellent properties such as heat resistance, flame retardancy, and mechanical properties are obtained, and meta-type wholly aromatic polyamide fibers having low residual solvent, high breaking strength, high elongation, and good dyeability and ease of dyeing are obtained. When used as a fabric, the high strength and high elongation provide protection and flexibility, leading to improved texture and comfort. A textile product having the desired design can be easily obtained by dyeing treatment. In addition, the low residual solvent content not only suppresses coloring and yellowing of the fiber in a high-temperature atmosphere, but also has no adverse effects on the human body when used for clothing. Furthermore, since the production method of the present invention requires only control of the water washing temperature, no complicated conditions or operations are required, and the conventional wet coagulation method can be adopted, so that the industrial value of the method is extremely great.

Claims

1. A meta-type wholly aromatic polyamide fiber, characterized in that the fiber has a breaking strength of 4.0 cN / dtex or more as specified in JIS-L-1015, a toughness value expressed by the square root of the product of the breaking strength and breaking elongation of the fiber of 15.0 or more, an amount of solvent remaining in the fiber of 0.1 mass % or less, and a dye exhaustion rate of 90% or more as measured by the following method. (dyeing rate) A dye solution containing 6% owf of a cationic dye (manufactured by Nippon Kayaku Co., Ltd., product name: Kayacryl Blue GSL-ED (B-54)), 0.3 mL / L of acetic acid, 20 g / L of sodium nitrate, 70 g / L of benzyl alcohol as a carrier agent, and 0.5 g / L of a dyeing assistant (manufactured by Meisei Chemical Industry Co., Ltd., product name: Disper TL) as a dispersant is prepared. Subsequently, a dyeing process is carried out for 60 minutes at 120° C. with a bath ratio of the fiber to be measured to the dyeing solution of 1:

40. After the dyeing process, reduction cleaning is carried out for 20 minutes at 80° C. with a bath ratio of 1:20 using a treatment solution containing 2.0 g / L of hydrosulfite, 2.0 g / L of Amylazine D (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: Amylazine D), and 1.0 g / L of sodium hydroxide, and the fiber is washed with water and dried to obtain a dyed fiber. The same volume of dichloromethane is added to the dyeing residual liquid after dyeing the fiber to be measured, and the residual dye is extracted. The absorbance of the extract is then measured at wavelengths of 670 nm, 540 nm, and 530 nm, and the dye concentration of the extract is determined from the calibration curves for the above three wavelengths, which were created in advance from a dichloromethane solution with a known dye concentration, and the average value of the concentrations at the above three wavelengths is taken as the dye concentration (C) of the extract. Using the dye concentration (Co) before dyeing, the value obtained by the following formula is defined as the dye exhaustion rate (U). Dyeing rate (U) = [(Co-C) / Co] x 100

2. 2. The method for producing meta-type wholly aromatic polyamide fibers according to claim 1, wherein in the solution spinning having a step of washing the fibers with water, the water temperature difference during the washing step is 40° C. or more.

3. 3. The method for producing meta-type wholly aromatic polyamide fibers according to claim 2, comprising at least two water washing steps, the latter of which has a water temperature at least 40° C. higher than that of the former.

4. 4. The method for producing meta-type wholly aromatic polyamide fibers according to claim 3, wherein in the two successive water washing steps, the water temperature in the latter step is at least 40° C. higher than the water temperature in the immediately preceding preceding step.

5. The method for producing a meta-type wholly aromatic polyamide fiber according to any one of claims 2 to 4, wherein the fiber is obtained by a wet spinning method in which a meta-type wholly aromatic polyamide having a weight average molecular weight of 200,000 to 600,000 is used, and an amide-based polar solvent solution containing 1.0 to 10.0 mass% of an inorganic salt is spun out and then coagulated, and the method further comprises a step of washing the fiber with water (water washing step).

Citation Information

Patent Citations

  • JP1960-014399B

  • JP1973017551B1

  • Aromatic polyamide fiber and its production

    JP1987184127A

  • Easily dyeable meta-aromatic polyamide fiber

    JP1996081827A

  • Method for producing meta wholly aromatic polyamide yarn and yarn obtained by the method

    JP2001303365A